2017
DOI: 10.5039/agraria.v12i4a5466
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência agronômica de fertilizantes organominerais líquidos em batateira, cultivar Asterix

Abstract: RESUMOA cultura da batata é a que mais exige a utilização de fertilizantes, em relação a todas as outras culturas produzidas no Brasil. Por isso é importante realizar estudos com novas fontes que possam potencializar o balanço entre nutrientes, melhorar a qualidade física do solo, fornecer nutrientes de acordo com as necessidades da planta e reduzir impactos ambientais. Objetivou-se avaliar a eficiência agronômica de fertilizantes organominerais líquidos em batateira, cultivar Asterix. O delineamento utilizado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The association between organic acids and nutrients was favorable to the productivity of the class with the highest commercial value and total productivity. The results of the application of OMF to the productivity of several species have been reported in the literature (Ferreira et al, 2022;, including potato cultivation with pelleted OMF (Cardoso et al, 2015) and liquid OMF (Souza et al, 2017). Cardoso et al (2017) applied pelleted OMF in planting and observed a 22% higher productivity than mineral fertilizer, which corroborates the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The association between organic acids and nutrients was favorable to the productivity of the class with the highest commercial value and total productivity. The results of the application of OMF to the productivity of several species have been reported in the literature (Ferreira et al, 2022;, including potato cultivation with pelleted OMF (Cardoso et al, 2015) and liquid OMF (Souza et al, 2017). Cardoso et al (2017) applied pelleted OMF in planting and observed a 22% higher productivity than mineral fertilizer, which corroborates the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The mixing of several products with different sources and nutrients can promote deleterious effects in the production of potatoes, as reported by Souza et al (2017). Soil contents, absorption capacity of crops, and the quantity contained in each product are extremely important since the imbalance between nutrients can generate competition in absorption sites, compromising the metabolic potential of plants.…”
Section: Discussionmentioning
confidence: 99%
“…When using methods such as fertigation or foliar fertilization, BF products in liquid form can be used. However, because the practice is still recent in horticulture, how these products act and influence plant growth, productivity, vegetable quality and the absorption dynamics (Souza et al, 2017) is not clear. Therefore, the objective of this study was to determine the nutrient accumulations and productivity of potato, cv.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of methods such as fertirrigation or foliar fertilization, OM products in liquid form can be used. However, because the practice is recent and the information still not clear, especially related to how these products act and influence the production of plants, in the productivity, in the quality of the vegetables and in the dynamics of absorption (SOUZA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%